Case Report: Acute effect of benralizumab on asthma exacerbation without concomitant corticosteroid use - Nolasco, Santi (F1000Res, 2020)
Background: Monoclonal antibodies are a relatively new therapeutic option for patients with severe refractory asthma, which can be used as an add-on to maintenance therapy, reducing the need for systemic corticosteroid usage, improving asthma symptom control and reducing exacerbations. We report a case of a patient with severe refractory eosinophilic asthma, reluctant to take systemic steroids, who was successfully treated with benralizumab alone during an acute asthma attack. Case presentation: A 59-year-old Caucasian woman with a history of allergic asthma since childhood showed a progressive decline in lung function with difficult to control symptoms and an increased number of hospitalizations despite maximal maintenance treatment, and was diagnosed with severe refractory asthma. She was reluctant to take systemic corticosteroids during exacerbations due to severe urinary retention; therefore, she started omalizumab with a partial reduction of symptoms and exacerbations over time. During a follow-up visit, she showed signs of acute exacerbation and she was switched to benralizumab during her acute phase with a rapid, dramatic amelioration of respiratory symptoms and pulmonary function, without concomitant systemic corticosteroid administration. During the treatment and at follow-up after one month, good tolerance and no side effects were observed. Conclusions: The use of benralizumab seems to be feasible, rapid, and safe in treating acute exacerbation of severe eosinophilic asthma without the use of systemic corticosteroids.